Attitude towards healthy nutrition and mental toughness: a study of taekwondo athletes - Ozsari, Arif; Kara, Mehmet; Dilek, Ahmet Naci; Uysal, Halil; Tek, Tolga; Deli, Sekip Can (Peerj Inc, 2024)
Healthy nutrition is widely considered the cornerstone of optimal athletic performance, both physically and mentally. This study investigates the critical role of healthy nutrition in shaping the physical and mental performance of athletes, with a specific focus on taekwondo. This research aims to explore the potential relationship between taekwondo athletes' attitudes towards healthy nutrition and their mental toughness. The research group comprised 276 active and licensed taekwondo athletes who voluntarily participated in the study (Age M = 17.18 +/- SD = 7.13, N = 125 women, N = 151 men). Ethical approval for the research was obtained prior to the commencement of the study. Data collection instruments included the Healthy Nutrition Attitude Scale, Mental Toughness Scale, and a personal information form. Confirmatory factor analysis was conducted to confirm the validity and reliability of the scales. Descriptive statistics, correlation analysis, and regression analysis were performed to explore the relationship between the variables within the research model. The correlation analysis identified two significant, positive, and moderate correlations: (1) between knowledge about nutrition and mental toughness (r = 0.626) and (2) between positive nutrition and mental toughness (r = 0.672). The regression analysis revealed that both knowledge about nutrition (/3 = 0.360) and positive nutrition (/3 = 0.461) significantly contribute to mental toughness. The findings suggest that as athletes' knowledge of nutrition expands and their attitudes towards healthy eating become more positive, their mental toughness also appears to improve. These results are both important and original, adding significant new insights to the existing research landscape.
Keywords: Nutrition; Healthy nutrition; Mental toughness; Athletes